Assessment of sensory attributes of value-added products of karonda (Carissa carandas) - Pooja Sharma; M R Choudhary; J P Yadav; Pushpa Ujjainiya; Mukesh Chand Bhateshwar; Mamta Yadav (Current Horticulture, 2025)
The study evaluated the sensory attributes of value-added products derived from Karonda (Carissa carandas L.) fruits focusing on the effect of fruit type and value added-product on overall organoleptic acceptance during (2022 and 2023) at S.K.N. Agriculture University, Jobner, Rajasthan. The Factorial Completely Randomized Design was used to analyse the data. Physiologically mature fruits were harvested, processed and evaluated by a panel of 15 members, using a 9-point hedonic scale for sensory attributes. The results indicated that maroon Karonda fruits consistently showed higher organoleptic acceptance scores compared to green fruits. Among value-added products, candy showed highest overall acceptance, while chutney the lowest. Significant variations in overall acceptance were observed, while candy made from maroon fruits showed the highest acceptance scores (8.40 and 8.47). The preserve prepared from green fruits showed lowest (7.28 and 7.43) acceptance during both the years. The study highlights the effect of fruit type and value-added products on sensory qualities, providing insights for optimizing karonda fruit-based products to enhance consumer preference.